(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
A comparison of the structure of the thyroid gland in its non-tumor pathology is described. The quantitative parameters of thyroid cells in macro-microfollicular colloidal nontoxic goiter, macro-microfollicular colloidal toxic goiter, diffuse toxic goiter and autoimmune thyroiditis were analyzed on the basis of histological material of patients. The features of the microstructure and dimensional characteristics of cells in each type of thyroid pathology were identified.